AB1032 FACTORS TO AID IN EARLY DIAGNOSIS OF KIKUCHI'S DISEASE IN ASIAN CHILDREN. (June 2019) - Pauline Chan Ng, Poh Lin; Lim, Lee Kean; Ang, Elizabeth; Ooi, Pei Ling
Abstract : Background: The diagnosis of Kikuchi's Disease (KD), also known as histiocytic necrotizing lymphadenitis, is often delayed as patients often undergo multiple investigations to exclude other causes of cervical lymphadenopathy, such as infection and malignancy 1 . Objectives: To describe the clinical features and treatment response of pediatric patients diagnosed with KD in our institution to aid early recognition. Methods: A retrospective study was conducted on patients < 18 years old diagnosed with KD in National University Hospital, Singapore, from Jan 2006 – Dec 2018. Demographics, clinical characteristics and treatment information were collected. Results: 14 patients were diagnosed with KD. All were Asian and majority were Chinese (64.2%). 57.1% were male and the age of presentation ranged between 2.8 to 17.9 years old. Fever duration at diagnosis ranged between 8 - 50 days. Median height of temperature was 39.8 (IQR: 39.4 – 40.0) deg C. This was frequently associated with neck pain and swelling (57.1%) and constitutional symptoms (71.4%) such as anorexia and weight loss. Other symptoms include abdominal symptoms of pain, vomiting or diarrhea (57.1%), rash (35.7%) and oral ulcers (28.6%). All patients had cervical lymphadenopathy either in the anterior cervical triangle or both anterior and posterior triangles, but not in the posterior triangle alone. This was usually multiple (92.9%), measuring ≥2cm in diameter (100%), tender (85.7%), and tended to be unilateral (64.3%); none had overlying warmth or skin changes. 14.3% had isolated hepatomegaly while 14.3% had hepatosplenomegaly. Common lab abnormalities included cytopaenias (50% bicytopaenia, 28.6% leucopaenia, 7.1% anaemia), elevated inflammatory markers C-reactive protein (CRP) (range: 12 – 117 mg/L), erythrocyte sedimentation rate (ESR) (range 15 – 116 mm/h) and lactate dehydrogenase (range: 480-1514 U/L). Only 3/14 had mild transaminitis. Interestingly, almost half had low alkaline phosphatase (ALP). All patients had normal to high complements and were negative for anti-dsDNA antibodies. Ultrasound of the neck typically revealed non-specific findings of reactive lymphadenopathy while 1 showed suspicious features of thickened cortex and loss of fatty hilum. 10/14 patients underwent excision biopsy which confirmed the diagnosis of Kikuchi Disease on histology. 3/14 did not have excision biopsy as they responded promptly to non-steroidal anti-inflammatory drugs (NSAIDs), one declined excision biopsy. All patients had received empiric antibiotics with no response. 64.3% required treatment with NSAIDs for an average of 2-4 weeks. Of the 4 patients who required steroid therapy, one was started at the diagnosis of KD, while the other 3 received steroids upon failure of NSAIDs. Response to either NSAIDs or prednisolone, if effective, was usually prompt, within 24 hours. Conclusion: Prolonged high grade fever with multiple tender cervical lymphadenopathy ≥ 2cm without warmth or redness and non-response to antibiotics, should raise concerns for KD. The presence of cytopaenia with moderately elevated inflammatory markers and LDH, coupled with low ALP, may be considered supporting biochemical features of KD. Prompt response to a trial of NSAIDs can help with the diagnosis of KD and potentially avoid excision biopsy of the lymph node. More research needs to be done to determine a clinical and biochemical diagnostic criteria for Kikuchi's Disease so as to aid early diagnosis and potentially avoid invasive excision biopsy of the lymph nodes. References: [1] Lin HC, et al. Kikuchi's disease in Asian children. Pediatrics. 2005 Jan;115(1):e92-6. [2] Chen CK, et al. Kikuchi disease in Asian children. J Paediatr Child Health. 2006 Mar;42(3):104-7. Disclosure of Interests: None declared